Cranial nerve involvement in typical and atypical chronic inflammatory demyelinating polyneuropathies. (23rd September 2020) - Shibuya, K.; Tsuneyama, A.; Misawa, S.; Suichi, T.; Suzuki, Y.; Kojima, Y.; Nakamura, K.; Kano, H.; Prado, M.; Kuwabara, S.
Abstract : Background and purpose: Cranial nerve palsy is occasionally present in patients with chronic inflammatory demyelinating polyneuropathy (CIDP), but its prevalence, characteristics and relations with the CIDP subtypes have rarely been investigated. The aim of this study was to systematically assess cranial nerve involvement in typical and atypical CIDP. Methods: Clinical data were reviewed in 132 consecutive patients with CIDP, including typical CIDP ( n = 89), multifocal acquired demyelinating sensory and motor neuropathy (MADSAM) ( n = 31), distal acquired demyelinating symmetric (DADS) ( n = 9) and others ( n = 3). Results: The frequency of cranial nerve palsy was 11% in typical CIDP, 48% in MADSAM and 11% in DADS. Facial and bulbar palsy was most frequently present (9%), followed by ocular motor nerve palsy (5%). Bilateral involvement was seen in all typical CIDP and DADS patients, whereas 80% of MADSAM patients had unilateral palsy. The presence of cranial nerve involvement was associated with more severe limb muscle weakness in typical CIDP, but not in MADSAM. Cranial nerve palsy fully recovered in 90% of typical CIDP and in 67% of MADSAM patients. Conclusion: Amongst the CIDP subtypes, cranial palsy is frequent and unilateral in MADSAM, and less frequent and bilateral in typical CIDP and DADS. In typical CIDP, facial and bulbar palsy reflects more severe and extensive inflammation.